General Viscosity Approximation Methods for Common Fixed Points of Nonexpansive Semigroups in Hilbert Spaces. (23rd December 2010) - Li, Xue-song; Huang, Nan-jing; Kim, Jong Kyu
Abstract : This paper is devoted to the strong convergence of two kinds of general viscosity iteration processes for approximating common fixed points of a nonexpansive semigroup in Hilbert spaces. The results presented in this paper improve and generalize some corresponding results in (X. Li et al., 2009, S. Li et al., 2009, and Marino and Xu, 2006).